PENGARUH KEPEMIMPINAN DAN SISTEM PENGHARGAAN TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Debora Silvia Hutagalung; Eko Deswin Miechaels Siringo-Ringo (Jurnal Ekonomi dan Bisnis (EK dan BI), 2021)
In the current era of globalization, every agency requires every employee to be able to improve their performance. The increase in performance is strongly influenced by the role of management in carrying out effective leadership. The failure or success that will be achieved by a company is influenced by leadership and is supported by adequate company capacity so that the company's goals will be achieved. On the other hand, leadership weakness is one of the causes of the collapse of a company's performance. This shows how big the role of leadership in a company is, so that a leader is expected to have the ability to motivate, direct, influence and communicate with his subordinates so that organizational goals can be achieved effectively and efficiently. This study was conducted to find out how the influence of leadership at the Indonesian Business Polytechnic on the performance of all employees consisting of lecturers/teaching staff, staff and employees, so that it is known how the reward system influences employee performance, and also to determine the effect of leadership and the reward system together. on job satisfaction with the method of direct observation on the object of research. In this study, the data used are primary data obtained by distributing questionnaires containing questionnaires to employees consisting of teaching staff, staff and employees at the Pematangsiantar Indonesian Business Polytechnic. The data analysis test used consisted of validity and reliability tests, classical assumption tests, namely data normality tests, multicollinearity tests, heteroscedasticity tests and research hypothesis tests, namely f test and t test.